Polyphenol Profiling by LC QTOF/ESI-MS and Biological Activity of Purple Passion Fruit Epicarp Extract - Monika Siniawska; Aneta Wojdyło (Molecules, 2023)
A polyphenolic preparation in the form of the passion fruit epicarp extract was analyzed to identify and quantify the polyphenolic compounds using LC QTOF/ESI-MS and UPLC-PDA-FL. The analyzed parameters included antidiabetic activity (α-amylase, α-glucosidase, and pancreatic lipase), inhibitory activity toward cholinesterase (AChE, BuChE), anti-inflammatory activity (COX-1, COX-2, 15-LOX) and antioxidant activity based on ORAC and ABTS. The polyphenolic preparation of the passion fruit epicarp extract contained 51 polyphenolic compounds representing five groups—flavones (25 compounds; 52% of total polyphenolic), flavonols (8; 16%), flavan-3-ols (6; 7%), phenolic acids (4; 3%), and anthocyanins (7; 21%), with derivatives of luteolin (13 derivatives) and apigenin (8 derivatives) as dominant compounds. The preparation was characterized by an antioxidant activity of 160.7 (ORAC) and 1004.4 mmol Trolox/100 mL (ABTS+o). The inhibitory activity toward α-amylase, α-glucosidase, and pancreatic lipase reached IC50 of 7.99, 12.80, and 0.42, respectively. The inhibition of cholinesterases (IC50) was 18.29 for AChE and 14.22 for BuChE. Anti-inflammatory activity as IC50 was 6.0 for COX-1, 0.9 for COX-2, and 4.9 for 15-LOX. Food enriched with passion fruit epicarp extract has a potentially therapeutic effect.